MONITORING THE INFLAMMATORY PROCESS OF FELINE LOWER URINARY TRACT DISEASE - Basma Mustafa; Heba Gouda; Ahmed Shehta; Tarek Shety (Slovenian Veterinary Research, 2023)
This study aimed to compare the hemato-biochemical parameters in cats suffered from FLUTD with those of healthy cats, and to evaluate the inflammatory process by measuring serum amyloid A, alpha-1-Acid glycoprotein, and plasma fibrinogen concentrations. Cats frequently suffer from feline lower urinary tract disease (FLUTD), which causes acute renal failure, electrolyte buildup, and acid-base imbalance. Acute-phase proteins can be used to monitor the inflammatory processes of feline lower urinary tract disease. The present study included thirty cats of both sexes, nine cats defined as clinically healthy cats and 21 cats with signs of idiopathic cystitis and/ or urethral obstruction for up to 24 hours were defined as cat with FLUTD group. Blood samples were collected from cephalic vein for hematological, biochemical assays and the measurement of acute-phase protein concentrations, including SAA, AGP, and fibrinogen. Serum SAA and AGP were measured using commercial ELISA kits. In cats with FLUTD, the total white blood cell count, neutrophils, and platelets count increased significantly, as did the mean values of hematological and biochemical indices. However, there was a significant decrease in the mean value of red blood cells, hemoglobin, and PCV. Blood urea nitrogen, creatinine, total proteins, albumin, potassium, and phosphorus levels all increased significantly, while sodium and chloride levels decreased significantly. When compared to clinically healthy cats, plasma fibrinogen, serum alpha-1- acid glycoprotein, and serum amyloid A levels were significantly higher in cats with FLUTD. There was a significant positive correlation between the concentrations of acute phase proteins biomarkers (SAA, AGP, and fibrinogen) and blood urea nitrogen and creatinine. It is concluded that, in cats with FLUTD, serum amyloid A, AGP, and fibrinogen could be employed as an indicator of inflammatory processes.